EFEKTIVITAS EDUKASI DIET TERHADAP KEPATUHAN DIET DAN KADAR GLUKOSA DARAH PADA PASIEN DM TIPE II POST RAWAT INAP DI RSUD dr. DORIS SYLVANUS PALANGKA RAYA - dewi, fretika utami; sugiyanto, sugiyanto; noraini, pepi (Jurnal Gizi dan Pangan Soedirman, 2022)
Type II diabetes is the most common type of diabetes suffered by patients due to changes in lifestyle. One way to improve patient compliance with treatment is by providing education about 3J which is useful for increasing knowledge so that blood glucose levels are kept under control. This type of research is quantitative using a cross sectional design with purposive sampling method. The number of samples was 22 patients with type II DM post hospitalization at RSUD dr. Doris Sylvanus Palangka Raya. Provision of dietary education is carried out when the patient is about to be discharged which is carried out by a hospital nutritionist. Data collection of compliance using a 3J questionnaire and blood glucose levels while using Easy Touch Strip Glucose with three measurements every two weeks. Analysis of the data using the Repeated Measures Anova test. The result showed that most sample characteristics being female (63.63%), age range being >56 years old (77.3%), the highest level of low education being 50%, and long suffering most DM with category > 5 years (68.2%). The results of this study indicate that the provision of diet education is effective on dietary compliance and blood glucose levels in post-hospitalized type II DM patients at dr. Doris Sylvanus Palangka Raya with a P-value 0.000 or (p<0.05) which can last up to two weeks